2021
DOI: 10.1186/s13195-021-00831-6
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer drugs repurposed for Alzheimer’s disease: a systematic review

Abstract: Background The relationship between cancer and dementia is triggering growing research interest. Several preclinical studies have provided the biological rationale for the repurposing of specific anticancer agents in Alzheimer’s disease (AD), and a growing number of research protocols are testing their efficacy and safety/tolerability in patients with AD. Methods The aim of the present systematic review was to provide an overview on the repurposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…They also target β -amyloid. The promising results of preclinical studies have triggered several clinical trials [ 2 , 3 ]. Moreover, Type 2 diabetes mellitus (T2D) has been identified as a high-risk factor for AD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also target β -amyloid. The promising results of preclinical studies have triggered several clinical trials [ 2 , 3 ]. Moreover, Type 2 diabetes mellitus (T2D) has been identified as a high-risk factor for AD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly acknowledged that certain OACDs may be effective against neurodegenerative and autoimmune diseases [ 9 , 108 ]. Nilotinib, a BCR-ABL tyrosine kinase inhibitor, has been investigated in multiple cases as a medication against mental disorders, such as Parkinson’s disease and Alzheimer’s disease [ 109 , 110 ]. The rationale of these indications is that nilotinib leads to the degradation of misfolded α-synuclein by autophagy [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, some anticancer drugs such as tyrosine kinase inhibitors and retinoid X receptor agonists can modulate cellular signaling pathways and reduce inflammation, which may be beneficial in the context of AD. Additionally, it has been shown that some anticancer drugs, such as histone deacetylase inhibitors, can improve cognitive function and synaptic plasticity in animal models of AD ( Ancidoni et al, 2021 ). Masitinib is an anti-tumor drug that has been investigated for potential use in the treatment of AD.…”
Section: Resultsmentioning
confidence: 99%